1991
DOI: 10.1002/jat.2550110112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential chemoprotectants against microcystin‐LR hepatotoxicity in mice

Abstract: Microcystin-LR (MCLR) is a potent cyclic heptapeptide hepatotoxin produced by the blue-green algae, Microcystis aeruginosa. Toxic blooms of this cyanobacteria have been reported throughout the temperate world. In spite of the potential economic loss and health hazard posed by this toxin, few studies on the development of an antidote have been conducted. Thus, a number of biologically active compounds were tested in mice for effectiveness in preventing the toxicity of a lethal dose of MCLR (100 micrograms kg-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 37 publications
(3 reference statements)
10
50
0
2
Order By: Relevance
“…These observations suggest that microcystin intoxication could be reduced or even prevented in the presence of Oatp/OATP substrates. They confirm previous studies that demonstrated complete protection of lethal intoxications in mice by the known OATP1B1 and OATP1B3 substrate rifampin (Hermansky et al, 1991;Vavricka et al, 2002). Therefore, one can speculate that any drug with reasonable high affinity for OATP, for example, statins (Hsiang et al, 1999), could prevent lowdose microcystin intoxication, provided it is given simultaneously with or shortly after the intoxication.…”
Section: Discussionsupporting
confidence: 88%
“…These observations suggest that microcystin intoxication could be reduced or even prevented in the presence of Oatp/OATP substrates. They confirm previous studies that demonstrated complete protection of lethal intoxications in mice by the known OATP1B1 and OATP1B3 substrate rifampin (Hermansky et al, 1991;Vavricka et al, 2002). Therefore, one can speculate that any drug with reasonable high affinity for OATP, for example, statins (Hsiang et al, 1999), could prevent lowdose microcystin intoxication, provided it is given simultaneously with or shortly after the intoxication.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the OECD 401 LD 50 protocol requires fasting of animals 24 h prior to oral dosing, with food ad libitum for up to 14 days post-dosing (observation period). If gastrointestinal as well as hepatic uptake of compounds, for example, MCs, is rate-limited via a carrier mediated uptake process (Eriksson et al, 1990a;Hermansky et al, 1990Hermansky et al, , 1991Hooser et al, 1991;Kuiper-Goodman et al, 1994;Kullak-Ublick et al, 1996;Meriluoto et al, 1990;Runnegar et al, 1991Runnegar et al, , 1995, the 24 h pre-dosing fasting period may not suffice to provide for a high bioavailability of the compound as the rodents will immediately resume consuming food during the observation period. Furthermore, the question arises whether the rodent food composition is comparable to the food composition generally applicable for humans, that is, whether the bioavailability of MCs is similar in rodent and in human food.…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Yea et al (2001) suggested that the immune system might be a direct target of MCs regardless of hepatocytes uptake of those compounds. Other reports have also indicated that the toxicity of MCs may influence the immune system (Hermansky et al, 1990(Hermansky et al, , 1991Stoner et al, 1990). To better understand the effects of MC-LR on fish immune system, ultrastructural changes of lymphocytes in the spleen and pronephros of grass carp Ctenopharyngodon idella were examined by transmission electron microscopy in this study.…”
Section: Introductionmentioning
confidence: 99%